Ball-Nogues Studio: Interview with Benjamin Ball - Benjamin Ball (Oz, 2009)
Benjamin Ball is a founding partner, along with Gaston Nogues, of Ball-Nogues Studio in Los Angeles. The staff conducted this interview in May 2009.